O Potencial dos campi das universidades públicas da microrregião bragantina paraense para o desenvolvimento local - ROCHA, Fernando de Carvalho (Universidade Federal do Pará, 2019)
Public universities, through their teaching, research and extension activities, play an essential role in the local development process. The objective of this study was to analyze the potential role of public universities, located in the bragantina microregion of the state of Pará, as agents promoting local development in the social, economic and environmental perspectives. The study is considered opportune by the presence of the progress provided by the relation of the academic environment to the activities of a locality. A study of the research environment was carried out with institutional and academic information about the university campuses of the paraense bragantina microregion. Documentary and bibliographical research was based on a review of the literature related to the theme of university and local development. With regard to the objectives, this research is classified as analytical and descriptive with quantitative nature by the use of descriptive techniques and statistics in the phases of data collection, treatment and analysis. The subjects of the research were the active servers in the campuses of the public universities of the municipalities of Bragança, Capanema and Igarapé-Açu. Data were also collected through the research and extension projects registered in the campuses of the micro-region studied and through municipal development indicators. The results revealed that the research and extension projects registered in the campuses of the researched universities are mostly classified within the social, economic and environmental dimensions of local development. Most participating servers consider their university campus to be extremely important or important in the context of local development. And we have shown superior results only in some indicators of municipal development of the municipalities of the bragantina microregion with the presence of a public university campus. It was concluded that the campuses of the public universities of the paraense bragantina microregion have great potential as catalysts for local development, especially in the social and environmental dimensions.